Resilience in parents of special needs children : appraisal and coping. - Wong, Joanne Weiyan. (2009)
This study investigates the process of resilience in parents with special needs children based on Lazarus’ Transactional Model of Stress (1990) which emphasizes the importance of subjective appraisal of stressor and wellbeing. The relationships between Perceived Caregiver Burden (PCB), coping styles on Caregiver Outcome (Subjective Wellbeing, General Health, Expectation of Child’s Outcome) were examined in 95 parents of special needs children. Support for the proposed Model of Resilience was found. PCB and Religion/Spirituality were predictors of decrease in parents’ SWB and GH. PCB was also a partial mediator of severity of Demand of Care on Caregiver Outcome, whilst Negative Emotion-Focused Coping partially mediated the effect of PCB on Caregiver Outcome. Overall, parents showed resilience in their roles as caregivers.